Influence of different timeframes of antibiotic application on postoperative infections in patients with caesarean section - Anhalt, Carolin; Kappelmeyer, Maurice; Cole, Georgia; Koeninger, Angela; Reuschel, Edith (Frontiers in Surgery, 2026)
Background/objectivesProphylactic, intravenous antibiotics are a known protective factor for surgery-related infections in patients undergoing caesarean section. This study aims to determine the impact of the timing of antibiotics and their influence on postoperative infection-related morbidity. Application 30 min before laparotomy was compared with application after umbilical cord clamping.MethodsThis study retrospectively analyzed the data of 6,034 patients giving birth by Caesarean section in University Clinic St. Hedwig, Regensburg. Germany. 3,001 cases (2017–2019) received a single shot of antibiotics 30 min before skin incision (Group 1), whereas in 3,033 women delivering by Caesarean section (2021–2023) the antibiotic was applied after cord clamping and child development (Group 2). Excluded were 62 cases for showing signs of infection before surgery or having a premature rupture of membranes prior to developing an infection.Results20 patients in each group developed surgery-related infections. The calculated Odds Ratio did not differ between groups. The risk for postoperative infection after Caesarean section was 1.6%.ConclusionsIn this study there was not found a significant difference between the two examined time points of antibiotic application in the numbers of postoperative infections. The results did not show an increased maternal risk for surgery-related infections by antibiotic application after cord clamping.